Rendimiento de una red definida por software (SDN) y una red tradicional de datos en aplicaciones de videojuegos en línea - Castañeda Valdiviezo, Jhonnatan David (2024)
In the new digital era, many online markets and technologies are created, modified, and evolved quickly since they are developed from easily accessible knowledge. However, there are technologies such as traditional data networks, which, due to market privatization, are sentenced to only innovate over time, making their integration and proper functioning increasingly more challenging. Non-profit organizations such as the Open Networking Foundation and the Linux Foundation are promoting research into an alternative network technology to the traditional one, called software-defined network technology, which wants to solve most of the shortcomings of conventional data networks, such as their low flexibility, low scalability, lack of innovation and difficulty in administration. Currently, one of the most demanding online markets in terms of quality of service is that of video games since a large part of their success depends on a good user experience, and to achieve this, they need the data network to offer low latency and connection stability. To understand the interaction of a video game with data networks, the performance of a software-defined network (SDN) and a traditional data network in online video game applications will be analyzed theoretically and practically by simulating two virtual environments that will reflect their behavior in a natural environment. Temporal data will be collected from both virtual environments to show statistically whether the change in network technology will improve the user experience in online video games.